Can a superabsorbent polymer help remediate compaction in frigid, semiarid soils? – a laboratory evaluation on soil physical processes. Issue 3 (3rd July 2021) - Ostrand, Megan S.; DeSutter, Thomas M.; Steele, Dean D.; Limb, Ryan F.; Daigh, Aaron L. M.
Abstract: Superabsorbent polymers (SAPs) absorb more water than their mass. When applied to frigid, semiarid soils, they may modify physical processes and amplify winter freezing-thawing effects for remediating compaction. If so, SAPs may be an effective amendment in reclamation projects. Laboratory tests evaluated SAPs influences on setting antecedent soil moisture and mechanical conditions prior to freezing-thawing. This was done by evaluating evaporation characteristics, water retention, and Atterberg limits on five soil series of differing textures as affected by SAP application rates (0, 40, 80, and 200 mg SAP kg −1 dry soil). Then, soil columns with and without freeze-thaw cycles were evaluated for each SAP rate to determine if SAP amplified freezing-thawing to remediate compaction. This was done by observing changes in soil bulk density, peak penetration resistance, and saturated hydraulic conductivity (Ksat) as indicators of compaction. Results demonstrated that increasing SAP rates significantly decreased evaporative water losses, increased water retention, and increased the liquid limit. In a field setting, these trends would set antecedent soil conditions that favor the remediation of compaction during subsequent winter freeze-thaw cycles. Results also demonstrated that SAP significantly affected the freezing-thawing process on some indicators of soil compaction. Increases in SAP rates significantly decreased peak penetration resistance, had mixed effects on Ksat, but no effect on bulk density. This suggests particle rearrangement is occurring internally (i.e., aggregation) even though changes in bulk density are not evident. Application of SAP appears to have potential for amplifying the remediation of soil compaction during winter in frigid, semiarid environments.